Training on Creating Interactive English Learning Activities Using Edpuzzle - Yunita Harita, Epifania Anggun; Waruwu, Julvin Oryentika; Enjelina Bate’e, Juni For; Telaumbanua, Yasminar Amaerita (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
The advancement of information and communication technology (ICT) has transformed the landscape of education, requiring pre-service teachers to develop strong digital pedagogical competence. This study describes a training program entitled ―Training on Creating Interactive English Learning Activities Using Edpuzzle‖ conducted for second-semester students of the English Education Study Program at Nias University. Using a qualitative descriptive design combined with a project-based learning (PBL) approach, the training aimed to improve students’ Technological Pedagogical Content Knowledge (TPACK) and ability to design interactive video-based media. Data were collected through observation, field notes, pre-tests, post-tests, and participant questionnaires. The results revealed a significant increase in students’ digital literacy, creativity, and confidence in integrating technology into English teaching. The average performance score improved from 42.5% before the training to 91.2% afterward. Students successfully created interactive English learning videos using Edpuzzle, embedding quizzes, voice notes, and reflective prompts aligned with TPACK principles. The findings support the Cognitive Theory of Multimedia Learning and demonstrate the effectiveness of project-based digital media training in enhancing 21st-century teaching skills. This program highlights the importance of structured, hands-on digital pedagogy training for pre-service English teachers to bridge the gap between theoretical knowledge and classroom practice.